Profiling Seventh-Grade Students’ Mathematical Connections in Rational Number Topics: A Study at an Islamic Integrated Junior High School in Pekanbaru - Azzahra, Sevilla Tita; Siregar, Annisa Fachraini; Wahyuni, Reni (EDUPEDIA Publisher, 2026)
Purpose – This study describes seventh-grade students’ mathematical connection ability in rational number topics at an Islamic Integrated Junior High School in Pekanbaru, prompted by recurring difficulties with cross-conceptual and contextual problem solving. Methodology – Using a descriptive qualitative design and purposive sampling, three Grade VII students were selected to represent high (DP), medium (KY), and low (IS) achievement. Data were gathered through a written test (three rational-number tasks) and in-depth interviews guided by NCTM (2000) mathematical connection indicators. Analysis included data reduction, indicator-based coding, test–interview triangulation, and conclusion drawing. Findings – DP satisfied all three indicators consistently. KY met some indicators but showed weaknesses in symbolization and contextual application. IS showed limited connections within mathematics, across disciplines, and to daily-life situations. Connection ability varied with conceptual understanding and independence, suggesting the need for more contextually and integratively focused instruction on rational numbers. Novelty – The study offers detailed qualitative profiles of mathematical connections in rational numbers across three distinct ability levels using NCTM (2000) indicators. Significance – Results support teachers, curriculum developers, and researchers in designing learning tasks and interventions that explicitly cultivate mathematical connections.